AKURASI METODE LAGRANGE DAN ORDINARY KRIGING UNTUK INTERPOLASI DATAMULTIVARIAT - Hery Andi Sitompul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Interpolate for function of several variables or multivariate data is still very limited discussed in literature. Would be very useful if help who compares the result of both scheme interpolate whether deterministic and stochastic. Lagrange method is one of the deterministic interpolaton scheme who determine a polynomial function to approach sample data, while Ordinary Kriging is one of the scheme stochastic interpolation who use the parameter of statistic sample data in neighbor point that will be interpolate. Both this scheme have the same result that very fine in interpolate points on multivariate data, although both of this method need different sample size.